Post Vaccination Myelitis in a Young Woman Following Administration of Rabies Chick Embryo Cell Vaccine - A Case Report (Ibrahim Medical College Journal, 2013)
A case of post-vaccination myelitis following administration of chick embryo cell rabies vaccine in a 20 year-old young lady is described. The case presented with paraplegia five days after receiving the third dose (on 12th day) of the vaccine for rabies. Myelitis was confirmed by signal changes on magnetic resonance imaging (MRI). She improved considerably on steroids treatment. This is the first case of myelitis following rabies chick embryo cell vaccination in Bangladesh. DOI: http://dx.doi.org/10.3329/imcj.v6i2.14738 Ibrahim Med. Coll. J. 2012; 6(2): 76-77